Anti‐inflammatory coatings of hernia repair meshes: A pilot study. Issue 2 (6th March 2017) - Gil, Dmitry; Rex, James; Cobb, William; Reukov, Vladimir; Vertegel, Alexey
Abstract: The current prevalence of postoperative chronic pain from hernioplasty procedures employing polymer mesh is close to 30%. Most of the researchers agree that oxidative stress, resulting from the release of oxidants and enzymes during acute inflammatory response, is a key factor in the development of posthernioplasty complications. This results in both the decrease of the biomechanical properties and stiffening of the polymer fibers of the mesh, leading to chronic pain. Moreover, enhanced activity of inflammatory cells can lead to an excessive deposition of connective tissue around the implant. In this study polypropylene hernia repair meshes coated with vitamin E (α‐tocopherol), a known antioxidant, were prepared and characterized. The absorption isotherm of vitamin E on the mesh was characterized and a release profile study yielded a promising results, showing sustained release of the drug over a 10‐day period. An animal study was conducted, and histological analysis five weeks after implantation exhibited a reduced host tissue response for a modified mesh as compared to a plain mesh, as evidenced by a higher mature collagen to immature collagen ratio, as well as lower level of fatty infiltrates, neovascularization and fibrosis in the case of modified mesh. These results support the use of α‐tocopherol as a potential coating in attempt to reduce the extent of postoperative inflammation, and thereby improve long‐term outcomes of hernioplasty. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 589–597, 2018.